Influence of extraction technology on rapeseed oil functional quality: a study on rapeseed polyphenols - He, Mengxue; Nian, Binbin; Shi, Jiachen; Sun, Xian; Du, Runfeng; Tan, Chin Ping; Xu, Yong Jiang; Liu, Yuanfa (Royal Society of Chemistry, 2021)
Extraction technology can influence the vegetable oil functional quality. Polyphenols in rapeseed oil have been proved to be beneficial for cardiovascular health. In this study, we evaluated the effect of extraction methods on the functional quality of rapeseed oil from the perspective of phenolic compounds. The results showed that hot pressing produces the highest amount of phenolic compounds in rapeseed oil. Its most abundant phenolic compound, sinapine (9.18 μg g−1), showed the highest activity in inhibiting anaerobic choline metabolism with an EC50 value of 1.9 mM, whose downstream products are related to cardiovascular diseases. Molecular docking and molecular dynamics (MD) simulations revealed that sinapine exhibits good binding affinity toward CutC, and CutC–sinapine is a stable complex with fewer conformational fluctuations and similar tightness. Taken together, hot pressing can be considered the best extraction method for rapeseed oil from the perspective of phenolic compounds.